Cost effectiveness analysis of expanding tuberculosis preventive therapy to household contacts aged 5–14 years in the Philippines - Ghassan Ilaiwy; Jessica Keim-Malpass; Romella Tuppal; Alexander F. Ritua; Flordeliza R. Bassiag; Tania A. Thomas (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2025)
Background: Children aged 5–14 years who are household contacts (HHCs) of index people with active TB disease (PWTB) have limited coverage for TB preventive therapy (TPT) due to variable uptake of the national guideline recommendations in the Philippines. We conducted a cost-effectiveness analysis evaluating the expansion of TB infection (TBI) testing and treatment among pediatric (5–14 years) HHCs of index PWTB in the Philippines to assist the National TB program in choosing the most cost-effective testing and treatment strategy for TBI among HHCs of index PWTB. Methods: Using a Markov state transition model, eligible HHCs age 5–14 years are screened for TBI with either the tuberculin skin test (TST) or interferon gamma release assay (IGRA). Those who test positive are then simulated to receive one of the following TPT strategies: 6 months of daily isoniazid (6H), 3 months of weekly isoniazid and rifapentine (3HP), 3 months of daily isoniazid plus rifampicin (3HR) and the current practice of no testing or treatment for TBI (NTT). The analysis assesses the projected cost and quality-adjusted life years (QALY) gained for every strategy from the perspective of the Philippines public healthcare system over a time horizon of 20 years. The total cost and gain in QALYs are presented as an incremental cost-effectiveness ratio (ICER) comparing cost per QALY gained for each strategy over NTT. Results: Our model estimates that expanding TPT coverage to HHCs aged 5–14 years would be cost-effective with incremental cost-effectiveness ratios (ICERs) ranging from 1,024 $/QALY gained when using TST and 6H (Uncertainty range: 497–––2,334) to 2,293 $/QALY gained when IGRA and 3HR are used (Uncertainty range: 1,140 – 5,203). These findings were robust to sensitivity analyses over a wide range of parameter values. Conclusion: Expanding TPT coverage to HHCs aged 5–14 years is cost-effective when using TST and 6H closely followed by a strategy combining TST and 3HP.